Colloquial Japanese - Clarke, H. D. B. (Routledge, 1981)
The new edition of this popular course in Japanese for beginners has been completely rewritten, to make learning Japanese as easy as possible. The course teaches Japanese script, though romanization is also included throughout for those who prefer to conentrate on the spoken language.